STUDENT’S AND TEACHER’S PERCEPTIONS OF AN «IDEAL ENGLISH LANGUAGE TEACHER» at SULEYMAN DEMIREL UNIVERSITY (Journal of Educational Sciences, 2018)
The paper presents a research study conducted at Suleyman Demirel University that aimed in investigatingthe perceptions of characteristics of an «Ideal English Language Teacher» by students andteachers. Those characteristics are divided into two categories of personal and professional qualities. Thesecond one includes such sub-categories as: English proficiency, pedagogical knowledge, organizationand communication skills, and socio-affective skills. The data were collected through the questionnairesamong 157 students and 17 ELT teachers at the faculty of Education and Humanities. The quantitativefindings revealed that students and teachers placed an importance on both qualities. However, therewere found statistic differences. Students perceive psychological skills as the most essential quality thatIdeal ELT teacher should have, in contrast according to teachers’ perceptions English Proficiency is consideredas highly necessary quality.Key words: ELT teacher, characteristics of ELT teacher, professional qualities, personal qualities.